User perceptions of rail public transport services in Kuala Lumpur, Malaysia: KTM komuter - Khalid, Ummi Aqilah; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor (Elsevier, 2014)
The needs for effective and efficient public transportation services are crucial to attract more people to use public transport, hence overcoming the issue of traffic congestion. Public transportation in Malaysia, including KTM Komuter, also facing various challenges, hence cannot offer the quality of services desired by passengers. This study aims to investigate the user perceptions towards KTM Komuter services. A survey conducted among the users during the weekdays and weekends. Findings showed three areas of their greatest concerns included services frequency, adherence to schedule and delays. Further, this paper highlighted KTM Komuter services that necessary and needed improvement.